Cultural resistance, 9/11, and the war on terror sensible interventions - Chao, Jenifer (Popular culture and world politics, 2018)
Cultural Resistance, 9/11, and the War on Terror: Sensible Interventions offers a fresh account of the enduring cultural legacies of the September 11, 2001 terror attacks and the global war on terror through the critical lens of cultural resistance. This book offers a new angle to consider the events of 9/11, the war on terror and their continual effects, one that blurs established visions of patriotism and grief.